2011
DOI: 10.1016/j.gie.2011.05.022
|View full text |Cite
|
Sign up to set email alerts
|

A double-masked, randomized, placebo-controlled trial of temporary endoscopic mucosal gastric electrical stimulation for gastroparesis

Abstract: Background Endoscopically placed, temporary gastric electrical stimulation (tGES) may relieve symptoms of gastroparesis (Gp) and predict permanent gastric electrical stimulation (GES) outcomes. Objective To measure effects of 72 hours of temporary GES on Gp symptoms. Design, Setting, and Patients From 2005 to 2006, we conducted a hospital-based, randomized, placebo-controlled, crossover trial of two consecutive, 4-day sessions (session 1 and session 2), enrolling 58 patients (11 males, 47 females; mean age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
87
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 97 publications
(89 citation statements)
references
References 21 publications
1
87
0
1
Order By: Relevance
“…In prior trials temporary GES predicted improvement with permanent GES and tGES has been validated using a double-masked crossover study. 10,21 Notwithstanding these limitations, our study demonstrated that temporary endoscopic GES is an effective therapy for gastroparesis and GLS. We also demonstrated a new possible entity of GLS categorized by RGE.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…In prior trials temporary GES predicted improvement with permanent GES and tGES has been validated using a double-masked crossover study. 10,21 Notwithstanding these limitations, our study demonstrated that temporary endoscopic GES is an effective therapy for gastroparesis and GLS. We also demonstrated a new possible entity of GLS categorized by RGE.…”
Section: Discussionmentioning
confidence: 77%
“…Patients/insurers paid for all costs, including temporary GES implantation and gastric scintigraphy studies with consecutive patients signing a consent for the protocol. The temporary GES system used in this study has been previously described 10 and includes an FDA approved temporary cardiac pacing lead (Medtronic model 6416), and an FDA approved implantable pulse generator (Medtronic 3116). Briefly, patients undergo upper endoscopy with a standard 140 cm long endoscope with a 7F accessory channel.…”
Section: Regulatory Approvalmentioning
confidence: 99%
See 1 more Smart Citation
“…11 However, in another study from the same group, vomiting and nausea improved both during on and off periods. 25 In a doubleblinded, randomized crossover study among 32 patients with idiopathic GP, nausea and vomiting improved non-significantly both with the stimulator on and off, but with a trend towards more improvement with the stimulator on. However, the lack of a washout period between the on and off phases may have compromised the data in the study.…”
Section: Discussionmentioning
confidence: 99%
“…GES has proven to be superior to placebo in 4 placebocontrolled trials in patients with diabetic, post-surgical, or idiopathic recurrent nausea and/or vomiting. 11,[23][24][25][26] In a double-blinded, randomized, crossover study, symptoms and quality of life improved significantly more while the stimulator was on than when off. 11 However, in another study from the same group, vomiting and nausea improved both during on and off periods.…”
Section: Discussionmentioning
confidence: 99%